Diseño de un plan de marketing estratégico para el posicionamiento de marca de calzado Gamos con el objetivo de incrementar su participación en el mercado de la ciudad de Quito. - Chimarro Chimarro, Verónica Vanessa (2015)
The present research is directed to footwear Gamos, which focuses on the manufacture of national shoes. This organization has generated several job opportunities over the years, thus improving life quality of the workers and their families. Gamos requires getting a better positioning and increasing its participation in the market in Quito through the creation of a marketing plan. The research carries out an internal and external situation analysis in order to identify its strengths, weaknesses, opportunities and threats and then evaluate the enterprise’s position in the market. A market research is also done through the application of surveys to know the characteristics of the target market. Gamos improvement of its different areas is carried out through SWOT analysis and market research. A sales increase has been the result of such practices. The strategies will be executed based on operational plans, using material, technological, economical, time and human resources.